Music as a Strategy for Character Development in Junior High School - Sagala, Mastri Dihita (Universitas Pendidikan Ganesha, 2024)
Music, with its various benefits, can serve as an effective strategy for instilling character values in education. This study examines the strategy applied through music, particularly in singing activities using the song “Mars Gembira Bergerak.” The research is descriptive and adopts a qualitative approach. Data analysis is conducted through the stages of reduction, presentation, and conclusion drawing. Data were collected through observations, interviews, and documentation, including the transcription of the song's notation to understand the lyrics and their meaning. The primary informant in this study is the song's creator. Triangulation techniques were used to evaluate the educational strategy implemented. The findings show that the song contains character values such as responsibility, enthusiasm, independence, creativity, and wisdom. The movements included in the singing activity are also essential for aligning with the character of junior high school students. The implications of this research suggest that teachers should create rhythmic movements in accordance with the music's rhythm. Additionally, the lyrics of the song incorporate the slogan of Bengkayang Regency, which teaches students to raise their thumbs while saying the word “mantap,” making this movement a part of the rhythmic activities that support character learning.